Application of low-cost Fe-based catalysts in the microwave-assisted pyrolysis of macroalgae and lignocellulosic biomass for the upgradation of bio-oil. (15th September 2021) - Dong, Yichen; Tian, Beile; Guo, Feiqiang; Du, Shilin; Zhan, Yinbo; Zhou, Huiming; Qian, Lin
Highlights: Steel slag and biochar-based Fe were prepared for microwave-heated biomass pyrolysis. Both steel slag and biochar-based Fe exhibited strong microwave absorbing ability. Steel slag significantly promoted the production of light compounds. Biochar-based Fe exhibited remarkable selectivity on Sargassum-derived bio-oil. Abstract: The combined application of microwave energy and special catalysts holds the potential for the selective conversion of biomass during the pyrolysis process. In this work, steel slag (SS) and biochar-based Fe (RHC/Fe) were adopted as both low-cost Fe-based catalysts and microwave absorbers in the microwave-heating pyrolysis system for the upgradation of bio-oil from macroalgae ( Sargassum ) and lignocellulosic biomass (pine sawdust). The catalysts all showed strong microwave adsorption performance, exhibiting higher heating rates than that of SiC. SS with a high content of iron oxides plays a catalytic role in biomass decomposition, while RHC/Fe with a highly porous structure not only promotes biomass decomposition but also enhances the secondary reaction of volatiles. The presence of SS significantly improved the content of lighter compounds (10 compounds) in Sargassum -derived bio-oil, leading to an improvement in the yield of potential chemicals such as phenols and furans; the formation of phenols was also significantly enhanced by SS during pine sawdust pyrolysis with a high phenols content of 55.8% in the obtained bio-oil. RHC/Fe exhibited remarkable selectivity on Sargassum pyrolysis and the obtained bio-oil contained only 13 compounds including 33.8% of 10 compounds and 66.2% of >C20 compounds without any C10 –C20 compounds. The N-containing compounds in Sargassum- derived bio-oil were successfully removed using RHC/Fe. RHC/Fe also showed a significant catalytic effect on the production of combustible gases from the pyrolysis of Sargassum and pine sawdust, with significant improvement in the total gas yields and combustible gas concentrations.